HER2-Positive Metaplastic Spindle Cell Carcinoma Associated with Synchronous Bilateral Apocrine Carcinoma of the Breast - Katsumi Kito; Toshiharu Maeda; Keiko Ninomiya; Atsuro Sugita; Teiri Sagawa; Kinya Matsuoka; Kousei Kinoshita; Naoki Hyodo; Nagisa Morita; Keizo Furuya (Case Reports in Pathology)
Apocrine carcinoma, which is strictly defined as over 90% of tumor cells showing apocrine differentiation, is a rare variant of breast cancer. Here we report an uncommon case in which apocrine carcinomas developed concurrently in both breasts; in addition, a sarcomatoid spindle cell lesion was coincident in the right breast. Both apocrine carcinomas were immunohistochemically negative for estrogen receptor (ER) and progesterone receptor (PgR), but diffusely positive for androgen receptor (AR), GCDFP-15, and HER2. The presence of intraductal components in bilateral carcinomas and the absence of lymph node metastasis suggested that they were more likely to be individual primary lesions rather than metastatic disease. The spindle cell lesion showed a relatively well-circumscribed nodule contiguous with the apocrine carcinoma. HER2 oncoprotein overexpression was observed not only in the apocrine carcinoma, but also in the spindle cell lesion. Since the spindle cell component was intimately admixed with apocrine carcinoma and had focal cytokeratin expression, we diagnosed it as metaplastic spindle cell carcinoma, which was originated from the apocrine carcinoma. To our knowledge, this is the first case report of a patient with synchronous bilateral apocrine carcinomas coinciding with metaplastic carcinoma.